2011
DOI: 10.1167/iovs.10-6907
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar Ocular Blood Flow Changes after Orbital Decompression in Graves' Ophthalmopathy Measured by Color Doppler Imaging

Abstract: In inactive moderate-to-severe GO, the RIs of the CRA and OA are higher than in normal subjects. The authors hypothesized that increased RIs of inactive GO may be due to orbital extrinsic compression of vascular structures because decompression surgery leads to decreases in the RIs of both the CRA and OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…After decompression surgery, the authors observed a significant decrease of calculable US parameters, such as resistive index (RI), which occurred in both ocular arteries mentioned above. These results may indicate that increased RI of inactive GO might be due to orbital extrinsic compression of vascular structures and decompression surgery leads to significant decreases of the RIs of different orbital arteries [30]. Moreover, Doppler ultrasound parameters of the retrobulbar arteries have been related to the clinical activity score, suggesting increased arterial blood flow velocity in patients with active GO due to inflammation of the orbital tissues [31].…”
Section: Ultrasound-based Imaging Evaluation Of Graves' Ophthalmopathymentioning
confidence: 93%
“…After decompression surgery, the authors observed a significant decrease of calculable US parameters, such as resistive index (RI), which occurred in both ocular arteries mentioned above. These results may indicate that increased RI of inactive GO might be due to orbital extrinsic compression of vascular structures and decompression surgery leads to significant decreases of the RIs of different orbital arteries [30]. Moreover, Doppler ultrasound parameters of the retrobulbar arteries have been related to the clinical activity score, suggesting increased arterial blood flow velocity in patients with active GO due to inflammation of the orbital tissues [31].…”
Section: Ultrasound-based Imaging Evaluation Of Graves' Ophthalmopathymentioning
confidence: 93%
“…Thyroid eye disease (TED) is characterized in most cases by an expansion in the fat and/or muscle in the orbit . Being an enclosed and fixed space, such alterations would be presumed to result in changes to intra‐orbital pressure and in compliance of the orbit, leading to decreased retrodisplacement of the orbit with supine positioning …”
Section: Ancova Modelmentioning
confidence: 99%
“…In normal subjects, the free flowing fat may allow for some compression when affected by increasing gravitational forces . However, the muscle‐involving TED orbit is less compliant and the stiffer tissue is thought to resist small changes in gravitational force. Furthermore, the generally elevated orbital and venous pressures in the supine position may lead to engorgement of the orbital tissues, and the small mean increase in proptosis was noted in this investigation.…”
Section: Ancova Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors induce and maintain the infl amma-from macrophages and tumor cells [ 12 ] . In TO, the restricted orbital compartment is associated with compression of orbital tissue and slow venous return [ 13 ] . This may result in a limitation in the oxygen supply, lower pH, and a higher concentration of lactate which could stimulate the proangiogenic factors expression, independently of other mechanisms such as infl ammation.…”
mentioning
confidence: 99%